Deterministic versus Random Utility: Implied Patterns of Vertical Product Differentiation in a Multi-Product Monopoly - Christiaan Behrens; Mark Lijesen; Eric Pels; Erik Verhoef (Tinbergen Institute, 2012)
In this article we study patterns of vertical product differentiation in a multi-product monopoly using a random utility model. Prior research shows that applying such a model in a multi-product setting implies symmetric patterns of product differentiation in which all product variants of a single firm have the same characteristics. Assuming that preferences differ across consumers and allowing for unobserved demand heterogeneity, we numerically show the existence of asymmetric, fully differentiated, patterns of vertical product differentiation in which the monopolist maximises profits by setting prices and qualities. In particular, we show that the patterns of vertical product differentiation depend crucially on the level of unobserved demand heterogeneity and the observed dispersion of willingness to pay for quality. Only if unobserved demand heterogeneity is small relative to the observed dispersion, asymmetric, fully differentiated, equilibriums exist. Furthermore, we find in our model that the level of unobserved heterogeneity and the dispersion of willingness to pay for quality do not affect the relative welfare efficiency of the monopolist.
urn:NBN:nl:ui:31-1871/38474
Keywords: D21; D42; L11; L12; 330; Vertical product differentiation; market segmentation; multi-product monopoly; random utility models; Produktdifferenzierung; Marktsegmentierung; Monopol; Theorie